Enhanced electro-optical response of nematic liquid crystal doped with functionalised silver nanoparticles in twisted nematic configuration. Issue 11 (1st September 2020) - S J, Shivaraja; Gupta, R K; Kumar, Sandeep; Manjuladevi, V
ABSTRACT: The dipolar and surface plasmon properties of metallic nanoparticles, especially gold and silver NPs made them suitable candidates for doping with LC system, which provides faster switching time, low power consumption in the display devices. The doping of NPs in the LC system influences the physical properties such as dielectric anisotropy, optical anisotropy, elastic constants, viscosity, and conductivity. In this work, we report the effect of doping of hexane thiol functionalized silver nanoparticles (f-AgNps) of average diameter 3-5nm on the electro-optical switching properties of nematic LC 4-trans-pentyl-cyclohexyl cyanobenzene (5PCH) in the twisted nematic geometry. The threshold as well as switching voltages have also reducedin the nanocomposites of 5PCH compared to pure 5PCH. The steepness of the V-T graph necessary for better multiplexing performance and high contrast has increased by 230% in the 0.025 wt% of f-AgNPs doped 5PCH compared to pure 5PCH. The ion current for 0.025 wt% f-AgNPs doped nanocomposites of 5PCH has reduced by 60% compared to pure 5PCH. We have observed faster switching time in f-AgNPs nanocomposites compared to pure 5PCH due to the decrease of visco-elastic ratio. The total response time of 0.05 wt% f-AgNPs nanocomposites is reduced by 19% compared to pure 5PCH. Graphical abstract: uf0001